2014
DOI: 10.1007/s12032-014-0885-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms at promoters of XRCC5 and XRCC6 genes and risk of breast cancer

Abstract: Variation in DNA repair genes is one of the mechanisms that may lead to variation in DNA repair capacity. Ku, a heterodimeric DNA-binding complex, is directly involved in repair of DNA double-strand breaks. Ku consists of two subunits, Ku70 and Ku80, which are encoded by the XRCC6 and XRCC5 genes, respectively. In the present study, we investigated whether common genetic variant in variable number of tandem repeats (VNTR) XRCC5 and T-991C XRCC6 was associated with an altered risk of breast cancer. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Additional eligible studies on this topic were identified by a hand search of references of retrieved articles. Studies testing the association between XRCC6 gene polymorphism and cancer were included if all the following conditions were met 5 , 8 – 14 , 16 , 20 – 30 : the publication was a case–control study; the study provided the total number of cases and controls; the study provided available genotype frequency in case and control group, respectively; the study was published in English. The major exclusion criteria were as follows: duplicate data 31 ; abstract, comment, review or editorial.…”
Section: Methodsmentioning
confidence: 99%
“…Additional eligible studies on this topic were identified by a hand search of references of retrieved articles. Studies testing the association between XRCC6 gene polymorphism and cancer were included if all the following conditions were met 5 , 8 – 14 , 16 , 20 – 30 : the publication was a case–control study; the study provided the total number of cases and controls; the study provided available genotype frequency in case and control group, respectively; the study was published in English. The major exclusion criteria were as follows: duplicate data 31 ; abstract, comment, review or editorial.…”
Section: Methodsmentioning
confidence: 99%
“…The subunits Ku70 and Ku80 are encoded by XRCC6 and XRCC5, respectively . The polymorphisms in these genes and the susceptibility to various cancers such as breast , hepatocellular and digestive system cancer have been reported. Human XRCC6 maps to chromosome 22 and specifically the rs2267437 polymorphism (C > G) is located in the promoter of the gene .…”
mentioning
confidence: 99%
“…XRCC5 encodes X-ray repair cross complementing 5 and functions as modulating chromosomal stability. It is down-regulated both in non-small cell lung cancer and breast cancer with hyper-methylation in promotor region; the SNPs in XRCC5 promoter region might be susceptible to breast cancer Rajaei et al 2014).…”
Section: Discussionmentioning
confidence: 99%